A Bloom's Taxonomy-integrated rotation model enhances clinical reasoning and practical skills in optometry interns during ophthalmology rotation: a randomized controlled trial - Cui, Yi; Wang, Li; Dong, Chenghuan; Cheng, Huiqin; Fu, Desheng; Hu, Jianzhang; Huang, Yan (Frontiers in Medicine, 2026)
Traditional clinical medical internship models often lack structured educational objectives and comprehensive assessments, limiting holistic competency development. This study evaluates the effectiveness of a novel internship education management model integrating Bloom's Taxonomy with a student-mentor rotation system to enhance cognitive, affective, and psychomotor skills. We conducted a randomized controlled trial with 54 optometry interns during their ophthalmology clinical rotation, assigning them to either an experimental group (n = 30) using the Bloom's Taxonomy-integrated rotation model or a control group (n = 24) receiving traditional training. Both groups completed 12-week rotations with identical duration and content. The Bloom's Taxonomy-integrated rotation model was organized into three progressive phases corresponding to ascending levels of Bloom's Taxonomy (knowledge acquisition → clinical application → synthesis). Outcomes were assessed through written examinations, practical skill test, and course experience questionnaires. The Bloom's Taxonomy-integrated rotation group showed superior performance in case analysis, history taking and practical skills. They also reported significantly higher satisfaction in problem-solving, motivation and feedback quality. In conclusion, the Bloom's Taxonomy-integrated rotation model demonstrated superior clinical reasoning, practical skills, and medical interns' satisfaction, among optometry interns compared to traditional training. The Bloom's Taxonomy-integrated rotation model represents an effective, structured framework for enhancing medical internship training, though warranting further validation in broader settings.